How Canadians Communicate III: Contexts of Canadian Popular Culture - Gloria Filax (Athabasca University Press, 2010)
What does Canadian popular culture say about the construction and negotiation of Canadian national identity? This third volume of How Canadians Communicate describes the negotiation of popular culture across terrains where national identity is built by producers and audiences, government and industry, history and geography, ethnicities and citizenships. Canada does indeed have a popular culture distinct from other nations. How Canadians Communicate III gathers the country's most inquisitive experts on Canadian popular culture to prove its thesis.